Leveraging crises into opportunities: European food banks in the time of covid, inflation, and war - Daniel N. Warshawsky (Discover Food)
Abstract Large food bank warehouses and their network of beneficiary organizations redistribute surplus food to charities across Europe. Since 2020, these food bank systems have faced a series of crises resulting from the covid pandemic, inflation, and the war in Ukraine. During the initial shock years of covid in 2020 and 2021, most food banks struggled to operate effectively due to increased demand, higher costs, inadequate resources, and uneven political support. Since then, the experiences of food bank systems have varied. While some food banks continue to struggle to redistribute food to their agencies, other food banks have scaled up their operations in size and scale. To understand these divergent outcomes, this research analyzes how food banks in the Czech Republic, Greece, and Portugal navigated through multiple crises in the years between 2020 and 2024. Findings in this study reveal how European food banks have leveraged crises to increase funding, surplus food, public legitimacy, political connectedness, and private sector support. The shocks between 2020 and 2024 provided an opportunity for some food banks to expand their operations or change how they deliver food to communities. However, even though food banks have increased their size and governance role in some contexts, the state and food industry shape what food banks can be and how they develop. In this way, food banks are limited by their neoliberal embeddedness within the broader food system.